Barriers to Receiving Tissue Plasminogen Activator in Patients with Ischemic Stroke - Mirzadeh, Monirsadat; Mozhdehipanah, Hossein; Emami, Ali; Motamed, Niloofar (Majallah-i dānishgāh-i ʻulūm-i pizishkī-i Qazvīn, 2021)
Background: Cerebrovascular diseases are the second common cause of mortality worldwide. The onset of reperfusion in the first 3-4.5 hours is a predictive factor of treatment. Objective: The present study investigated barriers to receiving tissue plasminogen activator in patients with ischemic stroke. Methods: This cross-sectional study examined 191 patients with first-ever stroke referring to the emergency department of the Persian Gulf Martyrs Hospital of Bushehr City, Iran, in 2016. One checklist was completed which included demographic data, history of diseases, knowledge of stroke symptoms, and intervals regarding the onset of symptoms to informing emergency, informing emergency on arrival at the emergency department of the hospital, and making the diagnosis for the patients. The obtained data were analyzed in SPSS v. 19. Results: Mean±SD age of the patients was 65.92±12.48 years. The majority of patients under investigation (55.5%) were female, 63.4% were married, 56% were illiterate and 72.3% resided in other districts of Bushehr province. Mean duration between onset of symptoms and arrival at emergency department, onset of symptoms and call the emergency service, time of arrival at emergency department to perform brain Computer Tomography (CT) scan and also to be counseled by a neurologist were 699.66, 195.51, 45.11 and 423.62 minutes, respectively. Finally 14.6 percent of patients were qualified to be treated with tPA. Conclusion: The main barrier to timely therapy is a delay in golden time. Therefore, public education to promote public awareness could be of great benefit in reducing the referral delay time.